5-2(x+3)=3-x

Simple and best practice solution for 5-2(x+3)=3-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-2(x+3)=3-x equation:


Simplifying
5 + -2(x + 3) = 3 + -1x

Reorder the terms:
5 + -2(3 + x) = 3 + -1x
5 + (3 * -2 + x * -2) = 3 + -1x
5 + (-6 + -2x) = 3 + -1x

Combine like terms: 5 + -6 = -1
-1 + -2x = 3 + -1x

Solving
-1 + -2x = 3 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-1 + -2x + x = 3 + -1x + x

Combine like terms: -2x + x = -1x
-1 + -1x = 3 + -1x + x

Combine like terms: -1x + x = 0
-1 + -1x = 3 + 0
-1 + -1x = 3

Add '1' to each side of the equation.
-1 + 1 + -1x = 3 + 1

Combine like terms: -1 + 1 = 0
0 + -1x = 3 + 1
-1x = 3 + 1

Combine like terms: 3 + 1 = 4
-1x = 4

Divide each side by '-1'.
x = -4

Simplifying
x = -4

See similar equations:

| logx=4.76 | | 2p-6=8+5(p+9) | | x+.07x=10000 | | x+.7x=10000 | | (4-x)(2x-5)=0 | | 4t=3t*3 | | 5K=2.5 | | 5(x+6)=4(x-7)+x | | 2(n+8)=16+2n | | 25-6x=11-8x | | 3xy-3x-y=0 | | 6x+6=-42-2x | | 8(x+2)+6=8x+7 | | -1=x^2-12 | | 5(3c-3)=4c+5 | | 6(k-7)-2=5 | | 1+12x=21+x | | a^2=744-x^2+x^2 | | 8ax+bx=0 | | 8ax+bx+28a^2x^2+8abx^2=-36 | | -3(6y-10)-y=-4(y-3) | | 10x+2x=156 | | 3(x-12)=12x | | 3a^2x^2+8abx+4b^2=-36 | | 3x+46=-4x(x+6) | | 8(2x-5)=15 | | 37x+6=6(6x+8) | | 2x-6x+4=x-2+6 | | 0=x^3-12x+1 | | 0.07x=1790 | | 3x+46=4x(x+6) | | 300x=630 |

Equations solver categories